Application of Business Model Canvas for Media Tech Startups VasTech - Nurul Arifin Aristarini (Journal of Research in Social Science and Humanities, 2025)
This research explores the application of the Business Model Canvas (BMC) framework in VasTech, a media technology startup in Indonesia, to enhance its business model and operational efficiency. Through a comprehensive situation analysis, primary data was collected via interviews with key executives, including the CEO and VP of Marketing, to understand the company's current business activities and challenges. The study reveals that the BMC facilitates a structured approach for startups to visualize their business models, enabling rapid adaptation to market feedback and fostering innovation. Ultimately, this research underscores the significance of the BMC as a dynamic tool for startups, providing insights into effective business model development and the potential for long-term success in a competitive landscape.